PENGARUH KEPEMILIKAN INSTITUSIONAL DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2012-2021) - Rita Satria; Tya Widyawati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
Institutional ownership is the ownership of shares of a company by institutions or institutions such as insurance companies, banks, investment companies, and other institutional ownership. Debt policy is a company policy in determining how much the company's funding needs are financed by debt. Based on the research results, institutional ownership has no effect on firm value. This is evidenced by the results of the t test obtained tcount of -3.417562 and ttable of 2.01174 with a significant level of 0.0013. In this study, with a significance <0.05 (0.0013 <0.05) and tcount <ttable (-3.417562 <2.01174). Based on the research results, debt policy has no effect on firm value. This is evidenced by the results of the t test obtained tcount of 1.465681 and ttable of 2.01174 with a significant level of 0.1494. In this study, with a significance > 0.05 (0.1494 > 0.05) and tcount <ttable (1.465681 <2.01174). Based on the results of the study simultaneously showed that the significant value was less than 0.05 (0.004589 <0.05) where the value of Fcount > Ftable (6.050832 > 3.20). The result of Adjusted R Square (R2) is R Square which has been adjusted, a value of 0.170920 or 17.09% indicates the contribution of the independent variable to the dependent variable.